Prevention Practice and Health Promotion A Health Care Professional's Guide to Health, Fitness, and Wellness. - Thompson, Catherine Rush, 1954- (SLACK, Incorporated, 2015)
The all-encompassing Second Edition of Prevention Practice and Health Promotion: A Health Care Professional's Guide to Health, Fitness, and Wellness offers foundational knowledge to health care professionals implementing primary, secondary, and tertiary prevention to healthy, at-risk, and disabled populations.